2024
DOI: 10.3390/curroncol31020075
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance: The Increased Risk of Cancers

Leszek Szablewski

Abstract: Insulin resistance, also known as impaired insulin sensitivity, is the result of a decreased reaction of insulin signaling to blood glucose levels. This state is observed when muscle cells, adipose tissue, and liver cells, improperly respond to a particular concentration of insulin. Insulin resistance and related increased plasma insulin levels (hyperinsulinemia) may cause metabolic impairments, which are pathological states observed in obesity and type 2 diabetes mellitus. Observations of cancer patients conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 275 publications
0
3
0
Order By: Relevance
“…A meta-analysis based on 37 studies for a total of more than 1.5 million subjects showed that metformin reduces the incidence of cancer in the liver (−78%), pancreas (−46%), colon (−23%), and breast (−6%), as well as mortality from liver and breast cancer [ 159 ]. The marked reduction in the incidence of certain types of cancer, such as those of the liver and pancreas, may be explained by the known fact that insulin resistance plays a pivotal role in their growth [ 160 ]. Of interest, a large meta-analysis of 121 cohorts, including more than 19 million individuals with about one million all-site cancer events, showed that T2DM is associated with an additional risk of all-site cancer of 6% higher in women than in men [ 161 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis based on 37 studies for a total of more than 1.5 million subjects showed that metformin reduces the incidence of cancer in the liver (−78%), pancreas (−46%), colon (−23%), and breast (−6%), as well as mortality from liver and breast cancer [ 159 ]. The marked reduction in the incidence of certain types of cancer, such as those of the liver and pancreas, may be explained by the known fact that insulin resistance plays a pivotal role in their growth [ 160 ]. Of interest, a large meta-analysis of 121 cohorts, including more than 19 million individuals with about one million all-site cancer events, showed that T2DM is associated with an additional risk of all-site cancer of 6% higher in women than in men [ 161 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus Higher all-cause mortality [122,123] Higher risk PAD [115][116][117] Higher RR for oral, stomach, and kidney cancers, and leukemia [160] Met: antihyperglycemic effect No difference [31] Met: pharmacokinetics No difference, considering weight difference and monitoring eGFR. [76] Met: ADRs Higher [23,24] Met: CRC-specific mortality * Lower […”
Section: Female Versus Male Referencesmentioning
confidence: 99%
“…It is supposed that hyperinsulinemia may play a role in tumorigenesis [4] even if the intimate mechanisms have not been completely elucidated. Recent observations in cancer patients have shown how Hypein may be a determining factor in influencing the development of obesity, diabetes, and cancer [34]. Both the insulin A receptor and the IGF-2 receptor mediate their effects through common oncogenic signaling pathways such as Ras/MAPK and β-catenin, which explains at least in part their involvement in carcinogenesis and the possibility that a chronic increase in circulating insulin levels leads to an increased risk of cancer in insulin-resistant subjects [35].…”
Section: Ir/hypein and Cellular Senescence And Cancermentioning
confidence: 99%